2019
DOI: 10.3390/app9183777
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Selenium-Enriched Yeast by Re-Using Discarded Saccharomyces cerevisiae from the Beer Industry for Se-Supplemented Fodder Applications

Abstract: Both inorganic and organic selenium (Se) can prevent and treat various diseases caused by Se deficiency. However, organic Se has less toxicity and a higher absorption rate than inorganic Se. In this study, inorganic Se (Na2SeO3) was bio-transformed into Se-enriched discarded beer yeast (Se-enriched DB-yeast) through fermentation accumulation by re-using discarded Saccharomyces cerevisiae from the beer industry for Se-enriched fodder application. Through a single-factor experiment and L9(34)-orthogonal test for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The content in commercial Se-enriched yeast is typically 500~2000 μg/g. Commercial yeast is generally S. cerevisiae discarded by the beer industry and processed for Se enrichment [ 27 ]. It has been reported that the enrichment site of Se in yeast is mainly concentrated in the sediment from protoplast fragmentation, and the Se content of this part accounts for more than 75% of the total Se content [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content in commercial Se-enriched yeast is typically 500~2000 μg/g. Commercial yeast is generally S. cerevisiae discarded by the beer industry and processed for Se enrichment [ 27 ]. It has been reported that the enrichment site of Se in yeast is mainly concentrated in the sediment from protoplast fragmentation, and the Se content of this part accounts for more than 75% of the total Se content [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Commercial yeast is generally S. cerevisiae discarded by the beer industry and processed for Se enrichment [ 27 ]. It has been reported that the enrichment site of Se in yeast is mainly concentrated in the sediment from protoplast fragmentation, and the Se content of this part accounts for more than 75% of the total Se content [ 27 ]. However, brewing materials, alcohol, and other metabolites often form high osmotic pressure in the process of beer production, which to some extent causes the plasmolysis in yeast.…”
Section: Resultsmentioning
confidence: 99%
“…These results were mainly due to the β-structure and irregular curl transition of the protein's turn to the α-helix structure in high Se concentration treatment. 41 Thus, Se treatment could significantly change the secondary and tertiary structures of Oryza sativa glutenin due to the replacement of sulfur on methionine and Cys by Se (Fig. 2).…”
Section: Preparation Purification and Identification Of Se-enriched P...mentioning
confidence: 97%
“…Se-enriched yeast can be obtained through growing yeast in Se-containing cultures. Commonly, a culture with 30 μg/mL Na 2 SeO 3 can result in Se accumulation in the range of 1200–1400 μg/g dried yeast ( Saccharomyces cerevisiae ), and the inorganic Se can be bio-transformed in yeast to form SePs [ 159 , 160 ].…”
Section: Selenoproteinsmentioning
confidence: 99%